Quantitative cerebral blood flow mapping and functional connectivity of postherpetic neuralgia pain: A perfusion fMRI study - Liu, Jing; Hao, Ying; Du, Minyi; Wang, Xiaoying; Zhang, Jue; Manor, Brad; Jiang, Xuexiang; Fang, Wenxue; Wang, Dongxin (Pain (Amsterdam), 2013)
This study investigated the postherpetic neuralgia pain-related brain regions and the underlying seed-based networks detected by arterial spin labeling. This article investigates the effects of postherpetic neuralgia (PHN) on resting-state brain activity utilizing arterial spin labeling (ASL) techniques. Features of static and dynamic cerebral blood flow (CBF) were analyzed to reflect the specific brain response to PHN pain. Eleven consecutive patients suffering from PHN and 11 age- and gender-matched control subjects underwent perfusion functional magnetic resonance imaging brain scanning during the resting state. Group comparison was conducted to detect the regions with significant changes of CBF in PHN patients. Then we chose those regions that were highly correlated with the self-reported pain intensity as “seeds” to calculate the functional connectivity of both groups. Absolute CBF values of these regions were also compared across PHN patients and control subjects. Significant increases in CBF of the patient group were observed in left striatum, right thalamus, left primary somatosensory cortex (S1), left insula, left amygdala, left primary somatomotor cortex, and left inferior parietal lobule. Significant decreases in CBF were mainly located in the frontal cortex. Regional CBF in the left caudate, left insula, left S1, and right thalamus was highly correlated with the pain intensity, and further comparison showed that the regional CBF in these regions is significantly higher in PHN groups. Functional connectivity results demonstrated that the reward circuitry involved in striatum, prefrontal cortex, amygdala, and parahippocampal gyrus and the circuitry among striatum, thalamus, and insula were highly correlated with each element in PHN patients. In addition, noninvasive brain perfusion imaging at rest may provide novel insights into the central mechanisms underlying PHN pain.